EFEKTIVITAS RESTITUSI KERUGIAN NEGARA DALAM TINDAK PIDANA KORUPSI DI BUMN BERBASIS KEMANFAATAN - Laila Mauluda Tunnisa; Usman, Ummi Farhah (Al-Daulah : Journal of Criminal Law and State Administration Law, 2025)
Research Objective: This study analyzes the effectiveness of state loss restitution in State-Owned Enterprise (SOE) corruption cases in Indonesia, employing utilitarian justice theory to diagnose barriers impeding asset recovery and to formulate a comprehensive utility-based reform framework. Research Method: An empirical juridical methodology with a descriptive-analytical qualitative approach was adopted, drawing upon court decisions, statutory instruments, institutional reports, and comparative international data from 212 SOE corruption cases documented by Indonesia Corruption Watch (ICW) between 2016 and 2023. Results: Aggregate state losses reached IDR 64 trillion (approximately USD 4 billion), yet asset recovery averaged merely 10.1% annually, well below international benchmarks, revealing five interconnected systemic failure dimensions. Findings and Implications: The identified failures encompass normative gaps in Article 18 of the Anti-Corruption Law, compounded by Law No. 1 of 2025 on SOEs; fragmented institutional coordination; weak digital forensic capacity; inadequate whistleblower protection; and the absence of non-conviction-based asset forfeiture mechanisms. These findings carry implications beyond Indonesia, extending to emerging-economy jurisdictions facing analogous SOE governance challenges. Conclusion: Ineffective restitution reflects systemic failure rooted in regulatory deficiencies, inter-institutional discoordination, and the absence of adequate legal instruments, necessitating a comprehensive, coordinated multi-pillar reform approach. Contribution: This study advances a utility-based restitution framework that repositions asset recovery as a social welfare instrument rather than mere fiscal accounting, encompassing regulatory reconstitution, establishment of an Asset Recovery Agency, blockchain-integrated monitoring, strengthened international mutual legal assistance, and public-benefit earmarking of recovered assets. Limitations and Suggestions: Reliance on publicly available documents potentially omits undocumented cases, while the qualitative approach limits statistical generalizability. Future research should pursue cross-country empirical comparisons, concrete blockchain-based monitoring pilots, and a systematic evaluation of the effects of Law No. 1 of 2025 on anti-corruption governance.